A case study of oral linguistic error-treatment in second language classrooms where English is the medium of instruction - Mntambo, Nomawabo (Rhodes University, Faculty of Education, Department of Education, 1995)
One of the issues that have been debated at length in second language acquisition research circles is that of error-feedback and its desirability. Although there is as yet no conclusive evidence concerning its effectiveness in contributing towards the acquisition of a second language, a number of studies that have been conducted bear evidence to its desirability in L2 classrooms. This research then, was concerned with the way teachers of content subjects reacted to their learners' linguistically erroneous responses during oral interaction in their classes. The participants were four teachers who, with their pupils, are second language speakers of English . Three of these were content subject teachers while the fourth one teaches English. The data was collected from a class of Std 5 pupils in a rural school in the Eastern Cape where the lessons of these teachers were observed and audio-taped. Subsequently some of them were transcribed and analysed. The analysis of the data revealed that teachers in content subject classes, who teach through the medium of English showed more concern for content than for linguistic errors despite the fact that they are expected to extend the pupils' chances of second language acquisition.
Keywords: Second language acquisition Language and languages -- Study and teaching; English language -- Errors of usage